2017
DOI: 10.1016/j.gaitpost.2016.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry in gait pattern following tibial shaft fractures – a prospective one-year follow-up study of 49 patients

Abstract: In patients treated by intramedullary nailing following a tibial shaft fracture, gait asymmetry accompanied with slower speed and cadence are common during the first 6 months and become normalized compared with a healthy reference population between 6 and 12 months post-operatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…GA was assessed by comparing the swing times performed by one leg with respect to the swing times performed by the other, according to the following formula: GA = 100 × | ln(SSWT/LSWT) | , where SSWT and LSWT were the mean values of the swing times for the legs with the shortest and longest mean swing times, respectively 9 , 10 . We calculated the GA using this method, as it has commonly been used in previous studies 45 , 46 . Using this definition, a value of 0.0 reflected perfect symmetry, and higher values reflected greater degrees of asymmetry 9 .…”
Section: Methodsmentioning
confidence: 99%
“…GA was assessed by comparing the swing times performed by one leg with respect to the swing times performed by the other, according to the following formula: GA = 100 × | ln(SSWT/LSWT) | , where SSWT and LSWT were the mean values of the swing times for the legs with the shortest and longest mean swing times, respectively 9 , 10 . We calculated the GA using this method, as it has commonly been used in previous studies 45 , 46 . Using this definition, a value of 0.0 reflected perfect symmetry, and higher values reflected greater degrees of asymmetry 9 .…”
Section: Methodsmentioning
confidence: 99%
“…GA was assessed by comparing the swing times performed by one leg with respect to those performed by the other, following the formula: GA = 100 x | ln(SSWT/LSWT) | where SSWT and LSWT were the mean values of the swing times for the leg with the short and long mean swing time, respectively[2,7]. We calculated the GA using this method because this has been commonly used in previous literature [4,5]. With this definition, values of 0.0 reflect perfect symmetry and high values reflect greater degrees of asymmetry [3].…”
Section: Methodsmentioning
confidence: 99%
“…This metric was used to quantify the ability of subjects to coordinate left-right stepping on level ground [7]. GA and PCI have been used as an indicator of different orthopedic diseases or status after surgery [46].…”
Section: Introductionmentioning
confidence: 99%
“…They had patients walk over a pressure‐sensitive mat which uses temporal‐spatial parameters to describe gait and found asymmetries within the fractured leg at 6 months with 12.8% shorter single support, 12.8% longer swing time, 11.9% shorter step length, and 32.3% increased foot rotation. By the end of 12 months, the observed gait asymmetries were almost corrected 5 . While the results of the study by Larsen et al produced good results at 12 months follow‐up, other functional outcome studies have shown that 44%–86% of patients continue to experience anterior knee pain even after their fractures are fully healed 11–20 .…”
Section: Introductionmentioning
confidence: 94%
“…Tibial diaphyseal fractures are most commonly surgically repaired with intramedullary nailing (IMN). While there are a number of studies using gait analysis to assess fracture outcomes, 2–4 literature evaluating functional ability and gait patterns following IMN of tibial shaft fractures is scarce 5 . Three‐dimensional motion analysis describes segmental gait patterns of the whole lower extremity using temporal‐spatial, kinematic, and kinetic parameters.…”
Section: Introductionmentioning
confidence: 99%